ANALYTICAL ACTIVITY AS A MEANS FORMATION OF REFLECTIVE SKILLS STUDENTS OF PEDUNIVERITY (Pedagogy of Higher and Secondary Education, 2007)
One of aspects of educational activity of students of pedagogical universities, which matters important in forming of reflections abilities of future specialists, is examined in the article.